The Effect of Executive Compensation, Executive Risk Preference, and Tax Incentives on Tax Avoidance - Ariyanto, Theresia Ivana; Weli, Weli (AJAR, 2025)
This study aims to analyze the effect of executive compensation, tax incentives, and executive risk preferences on tax avoidance. The data collection technique uses purposive sampling with entities from the manufacturing sector. The results of data collection were obtained from 96 companies with a period of two years, namely 2022 and 2023. The tool that supports the processing process in data analysis is SPSS Version 27 software. The results of the study revealed that executive compensation and tax incentives do not have a significant effect on the phenomenon of tax avoidance. On the other hand, risk preferences or executive character have a significant effect on tax avoidance actions. This study combines agency theory and planned behavior theory to understand the causes of tax avoidance. The theoretical impact of the study is to enrich the literature on tax avoidance by adding the perspective of executive risk preferences as the main influencing factor. Furthermore, this study also confirms the relevance of agency theory and planned behavior theory. Practically, the findings in this study can be a reference for various parties who are designing more effective policies.